Der «Regionalpark” als Handlungsfeld der Metropolitan Governance: Eine Realisierungs-Analyse am Beispiel der Zürcher Glattal-Stadt - Gabi, Simone; Thierstein, Alain (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
Several Metropolitan Regions in Germany have adopted Regionalpark Concepts as a strategy to develop open spaces. In Switzerland there is a lack of actively governing and shaping open spaces in urbanised landscapes. The chances and obstacles to realizing a Regionalpark in Switzerland have been analysed based on a case study in the Zurich Glattal Region. The study considers the creation of a Regionalpark as afield of action for Metropolitan Governance. In order to perform Metropolitan Governance succesfull three strands of activity are proposed to be taken into consideration: strategies, structures and the culture of Governance.